Considerations on ecological aspects and conservation status of Pinguicula jackii subsp. jackii (Lentibulariaceae), an endangered species from south-central Cuba - Vasallo Rodríguez, Leosveli; Montes, Rosalina; Escarré Esteve, Antonio; León Cabrera, Julio; Bonet Jornet, Andreu; Alomá Moreno, Omar (Instituto de Ecología, A.C., 2018)
Background and Aims: The genus Pinguicula comprises plants with specific ecological requirements. For Cuba, 13 species are reported, all of them endemic, restricted to plant formations on karst sands and in mountainous systems on karst, laterite and serpentine. Pinguicula jackii is found in the Guamuhaya Mountain System, south-central Cuba. Research on this species is focused on taxonomic studies with herbarium material and genetic tests, lacking information on its ecology. The objective of this work is to describe the ecology of P. jackii, update the information on its geographic distribution, conservation status, population dynamics, and evaluate the possible incidence of the land uses associated with the cliffs where it lives.Methods: The research was carried out from February 2015 to May 2016, in the watershed of the Mataguá River, Cienfuegos province, Cuba. We determined the extent of occurrence (13.36 km2), the area of occupancy (3.23 m2), the height of plants from the ground, substrate inclination, temperature, relative humidity, exposure, dimension of the patches with adequate habitat for the species and its occupation, as well as the coverage with photographic image processing.Key results: The presence of the species is confirmed in three subpopulations and a new one is reported in the locality of Mundo Nuevo. All of them are associated to traditional abandoned coffee plantations and/or horticultural crops. The kind of soil use influenced the size of the subpopulations and occupation area of P. jackii.Conclusions: The traditional shade-grown coffee plantation is an agricultural activity that did not compromise the conservation of the species. The horticultural crops could be affecting the population sizes, due to intensive tillage and handling such as burning, clearing and use of phytosanitary products. The species meets the UICN criteria to be considered as Critically Endangered.